2021
DOI: 10.21203/rs.3.rs-307295/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glaucoma Profile at the Tertiary Ophthalmic Centers in Ankara, Turkey

Abstract: Purpose: This study aimed to investigate the demographic and clinical characteristics of the patients with glaucoma, who presented at the tertiary ophthalmology clinics in Ankara, Turkey.Patients and Methods: This cross-sectional study included all of the consecutive glaucoma patients or glaucoma suspects who presented at ten different tertiary ophthalmology clinics in Ankara between March 2015 and May 2015. The demographic characteristics and clinical findings of the patients were evaluated. Glaucoma was diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…19 Few studies were conducted on populations with Middle Eastern descent, which reported a higher prevalence of POAG followed by both PACG and PSXG. 20,21 In the Gulf region, two community-based studies were carried out in Oman and Qatar, which reported POAG as the most prevalent type, followed by PACG. 22,23 Our study revealed that the most common subtype of glaucoma was PACG, and this was in line with two other hospital-based studies that were conducted in Riyadh 7 and Qassim 10 provinces.…”
Section: Discussionmentioning
confidence: 99%
“…19 Few studies were conducted on populations with Middle Eastern descent, which reported a higher prevalence of POAG followed by both PACG and PSXG. 20,21 In the Gulf region, two community-based studies were carried out in Oman and Qatar, which reported POAG as the most prevalent type, followed by PACG. 22,23 Our study revealed that the most common subtype of glaucoma was PACG, and this was in line with two other hospital-based studies that were conducted in Riyadh 7 and Qassim 10 provinces.…”
Section: Discussionmentioning
confidence: 99%